A new technique for deep in situ measurements of soil water retention behaviour. Issue 1 (19th January 2018) - Rocchi, Irene; Gragnano, Carmine Gerardo; Govoni, Laura; Mentani, Alessio; Bittelli, Marco; Castiglione, Paolo; Buzzi, Olivier; Gottardi, Guido
Abstract : In situ measurements of soil suction and water content in deep soil layers still represent an experimental challenge. Mostly developed within agriculture-related disciplines, field techniques for the identification of soil retention behaviour have been so far employed in the geotechnical context to monitor shallow landslides and seasonal volume changes beneath shallow foundations, within the most superficial ground strata. In this paper, a novel installation technique is presented, discussed and assessed, which allows extension of the use of commercially available low-cost and low-maintenance instruments to characterise deep soil layers. Multi-depth installations have been successfully carried out using two different sensor types to measure the soil suction and water content up to 7 m from the soil surface. Preliminary laboratory investigations were also shown to provide a reasonable benchmark to the field data. The results of this study offer a convenient starting point to accommodate important geotechnical works such as river and road embankments in the traditional monitoring of unsaturated soil variables.